Pokaz Rybacki. (Gdynia : [s.n.], 1946)
Afisz inf. o pokazie, który miał miejsce w Gdyni 7.09-15.09.1946 r.
Keywords: Gdynia (Polska) -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- plakaty; Gdynia (Polska) -- 1945-1970 -- źródła